Solid Utopias. Views and Models in Urban Experimentation in the 1960s (diségno, 2021)
This contribution presents an analysis of several design experiences developed primarily between the late 1950s and early 1970s which constituted a true international trend where the issues of representation constituted a visionary thought that proposed original architecture and urban forms.The communicational devices aim to clarify the diverse formal characteristics, often highlighting a ‘possible realism’. Modifications, superposition, and experimentation are thus reflected in the processes of representation. Graphically, the choice fell mainly on the means appropriate for solving complexity and innovation: the use of collage and photomontage fundamentally adheres to meeting these needs.The contribution of models is also effectively highlighted with the inclination of plastic figuration to oscillate between the abstraction and simulation of reality. There are models that, emphasizing realism and with the goal of mitigating the most imaginary nature of innovative urban hypotheses, are presented somehow as the anticipation of reality and a testimony to their possible ‘buildability’. The model itself, with its special characteristics, often becomes a research tool; many examples contain references to the historical avant-garde, even through an aesthetic search that manages to combine experimentation with communication of the design thought.
Keywords: utopian architecture; experimental architecture; architectural models; architectural representation